Paul Ricoeur and narrative context and contestation - Joy, Morny (EBSCOhost eBook Collection, 1997)
From a poetics of the will to narratives of the self: Paul Ricoeur's Freud and philosophy Jocelyn Dunphy Blomfield -- Dietrich Bonhoeffer, Letters and papers from prison and Paul Ricoeur's "Hermeneutics of testimony Jamie S. Scott -- Role of figure in metaphor, narrative and architecture Graham Livesey -- Writing as repossession: the narratives of incest victims Morny Joy -- Re-reading myth in philosophy: Hegel, Ricoeur and Irigaray reading Antigone Pamela Anderson -- Narration and life: on the possibilities of a narrative psychology Henderikus J. Stam and Lori Egger -- Women's memoirs and the embodied imagination: the gendering of genre that makes history and literature nervous Helen M. Buss -- Narrative songs and identity in late-medieval women's religious communities Hermina Joldersma -- On narrative and belonging David D. Brown -- Quebec narratives: the process of refiguration Dominique Perron -- Ricoeur and political identity Bernard P. Dauenhauer -- Essay/ing Ricouer: a challenge to Ricoeur's construction of historical and fictional (and metaphorical) truth C. Bryn Pinchin -- Tragic face of narrative judgment: Christian reflections on Paul Ricoeur's theory of narrative James Fodor -- Narrative theology Post mortem dei? Paul Ricoeur's Time and narrative, III, and postmodern theologies Terrence W. Tilley -- Ricoeur on ethics and narrative Robert D. Sweeney -- Mediation, Muthos, and the hermeneutic circle in Ricoeur's narrative theory Linda Fisher